Kebijakan Fiskal dalam Perspektif Islam: Rekonstruksi Konseptual, Instrumen Syariah, dan Relevansinya terhadap Ekonomi Kontemporer dan Industri Halal: Fiscal Policy in Islamic Perspective: Conceptual Reconstruction, Sharia Instruments, and Their Relevance to Contemporary Economy and Halal Industry - Azwar Azwar; Andi Wawan Mulyawan; Amiruddin K. (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2026)
Fiscal policy constitutes a strategic instrument in national economic management that functions not only to maintain stability and promote economic growth, but also to realize social justice and public welfare. From an Islamic perspective, fiscal policy is grounded in the normative foundations of Sharīʿah and oriented toward the attainment of maqāṣid al-sharīʿah, particularly distributive justice and the promotion of public interest (maṣlaḥah ʿāmmah). This study aims to elucidate the fundamental concept of fiscal policy in Islam from both theoretical and historical perspectives; to analyze the principal Islamic fiscal instruments and their respective functions; to examine the strategic role of the Bayt al-Māl as the state’s fiscal institution; and to assess the relevance of Islamic fiscal policy in the context of the contemporary economy, including the strengthening of the Islamic economic sector and the halal industry. The research employs a qualitative–descriptive approach based on a library study, utilizing content analysis of classical and contemporary literature, regulatory documents, and relevant academic studies. The findings indicate that Islamic fiscal policy is built upon a strong and holistic normative foundation, with instruments such as zakāt, kharāj, jizyah, ʿushr, ghanīmah, fayʾ, and waqf functioning not only as sources of state revenue but also as mechanisms for redistribution and social protection. The Bayt al-Māl plays a central role as a public financial management institution and holds significant potential for revitalization within modern economic systems through transparent and integrated governance. This study affirms that Islamic fiscal policy remains relevant and strategic in addressing contemporary economic challenges, including social inequality and the development of the halal industry, thereby offering both a conceptual and practical alternative for the formulation of equitable and sustainable fiscal policies.